Learning to doctor: tinkering with visibility in residency training. Issue 4 (3rd October 2012) - Wallenburg, Iris; Bont, Antoinette; Heineman, Maas‐Jan; Scheele, Fedde; Meurs, Pauline
Abstract Medical doctors in teaching hospitals aim to serve the two central goals of patient care and medical training. Whereas patient care asks for experience, expertise and close supervision, medical training requires space to practise and the 'invisibility' of medical residents. Yet current reforms in postgraduate medical training point to an increasing emphasis on the measurable visibility of residents. Drawing on an ethnographic study of gynaecology training in The Netherlands, this article demonstrates that in daily clinical routines multiple practices of residents' visibility (visibilities) coexist. The article lists four visibilities: staging residents, negotiating supervision, playing the invisibility game and filming surgical operations. The article shows how attending physicians and medical residents tinker with these visibilities in daily clinical work to provide good care while enacting learning space, highlighting the increasing importance of visualising technologies in clinical work. Moreover, the article contributes to traditional sociological accounts on medical education, shifting the focus from medical education as a social institution to the practices of medical training itself. Such a focus on practice helps to gain an understanding of how the current reform challenges clinicians' educational activities.